The Struggle for Recognition: A Festive Perspective - Moyaert, Marianne (Philosophy & theology, 2010)
This article reflects on the struggle for recognition, in particular on the question of how to avoid people becoming battle-weary. Where do people find the strength to continue this struggle without lapsing into violence? These are questions which we derive from one of Paul Ricoeur’s latest publications Course of Recognition. Ricoeur claims that the only way to avoid the struggle for recognition degenerating into violent conflicts, is to place it in a horizon of hope—the hope that the struggle does not have the final word on interpersonal relations. In this article we take up Ricoeurs suggestion and elaborate it successively from a broad religious perspective and a Christian-Biblical perspective. This also allows us to develop new anthropological insights concerning the Struggle for Recognition.